Voltammetric characterization of a N,N'-diphenyl-p-phenylenediamine-loaded screen-printed electrode: a disposable sensor for hydrogen sulfide. - Lawrence, N; Jiang, L; Jones, T; Compton, R (2003)
The voltammetric response of a 10% (by weight) N,N'-diphenyl-p-phenylenediamine (DPPD) and 90% (by weight) carbon and binder screen-printed electrode has been examined in aqueous media over a range of pH using cyclic voltammetry both in the presence and in the absence of sulfide. In the absence, the screen-printed electrode undergoes an initial oxidative process on the surface of the solid organic particles to form an insoluble layer of the corresponding cation radical salt, DPPD(*)(+)X(-), where X(-) is an anion present in the solution. The charge transfer is thought to occur at the three-phase boundary between solid DPPD, carbon, and the aqueous solution. At higher potentials, a second oxidative wave is observed that is attributed to the oxidation of the bulk DPPD with intercalation of the anion species present to form a solid phase of DPPD(*)(+)X(-). The two voltammetric processes were found to stabilize after repetitive scanning, after which time, sulfide was added to the solution. The voltammetric response was found to respond to sulfide by showing a decrease in both the oxidative and reductive waves, which can be attributed to the sulfide effectively blocking the three-phase boundary. The response was found to be independent of the electrode used and at pH 4 produced a linear range from 20 to 165 microM, and a limit of detection of 7.5 microM for sulfide detection was achieved.